Letter (copy) - Vulliamy, Chloe
1938-03-13 038-0151-006 13th March, 1938. G.T. Garratt, Esq., Basque Children's Committee, 53, Marsham Street, S.W.1. Dear Mr. Garratt, In view of the fact that your Committee has never offered any explanation of the eye-witness account of events at the Franco-Spanish frontier, which appeared in the Daily Express some weeks ago, or any guarantee against a repetition of such events, and since it is now contemplating a large expedition of children to rebel territory, I feel it is my duty to ask the following questions:- 1. Are escorts now allowed to cross the frontier? 2. Have they absolute proof that children are really returned to their parents? 3. Is the British Consul at Bilbao making himself responsible for this as was suggested in a further report in the Express 4. Has news been received of the two older girls who were arrested at the frontier, and can assurances be given that this will not happen to other older children if they are allowed to return? 5. Has the Committee first-hand information as to the provision made for children whose parents are destitute? Unless satisfactory answers can be given to these questions within the next few days I shall feel morally compelled to take whatever measures may be necessary to prevent the return of children from this centre, and also to make a public protest against the action of your Committee in continuing to repatriate children to rebel territory. As I have not yet had the opportunity of laying this matter before my own Committee, I would like to make it clear that I am writing on my own responsibility as Warden of this centre, and not as their representative. Yours truly, 292/946/38/151(VI)